Society, Law and Economy: Contextualizing Ibn Khaldun's Thought - Jm Muslimin (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2019)
Economics and the law are the two inseparable things. There is always a relationship between the two. These two things can influence the development of people's welfare. This writing explores that during his life (1332-1406 AD), Ibnu Khaldun spent almost his whole time to read, learn and produce a distinctive work regarding socio-historical development of the existing government and community, as well as the type of local entity. Moreover, for some researchers, the role of Ibnu Khaldun in paving the way for creating foundations of sociological study can’t be neglected. According to him, the role of law in economic activity in general can be seen from two sides, in two equal interests, namely: a. Law is seen from the dimensions of economic activity; and b. Law is seen from the dimension of the state over its authority. Departing from the economic goals, in fact to obtain the maximum profit, the law is merely seen as a useful external factor and can be utilized to secure the economic activities and objectives to be achieved. The research proves that the essence of Ibnu Khaldun’s thought is still relevant to the modern time. Departing from his ideas and comparing them to the western and modern ones, one may conclude that Ibnu Khaldun’s philosophical analyses could be reinterpreted and contextualized. If it is so, then his theories are more identical to Stiglitz than to Smith and Marx.